1979
DOI: 10.1007/bf01281937
|View full text |Cite
|
Sign up to set email alerts
|

Radio wave phase method of quality control for refractory slabs for sliding gates

Abstract: In pouring steel from ladles, successful use has recently been made of sliding gate valves in which the crucial elements are refractory slabs [i]o These slabs operate in stringent conditions, and therefore severe technical requirements are imposed on them (TU [2]~ The present quality control of these slabs, which involves testing two specimens from each batch of 400 sets for mechanical strength and open porosity, is inadequate for reliable estimation of the production of crucial components.It is necessary to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

1987
1987
1987
1987

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…'2-0.3 g/cm 3, as the result of which the change in porosity within the limits of a single part is as high as 6% in absolute value [4][5][6][7]. A significant difference in density of parts frquently leads to the fact that the readings of the mechanical properties (open porosity, apparent density, compressive strength) determined on specimens are beyound the allowable limits although on the average for the part these readings are satisfactory.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…'2-0.3 g/cm 3, as the result of which the change in porosity within the limits of a single part is as high as 6% in absolute value [4][5][6][7]. A significant difference in density of parts frquently leads to the fact that the readings of the mechanical properties (open porosity, apparent density, compressive strength) determined on specimens are beyound the allowable limits although on the average for the part these readings are satisfactory.…”
mentioning
confidence: 99%
“…The results of investigationof the interrelationship between the dielectric permeability of refractory parts and their microstructure and strength properties [5,13,14] showed that there is a clear relationship between 8 and the compressive strength as the result of their common relationship to the change in apparent density. From the values of it is possible to determine other indices related to the change in Papp"…”
mentioning
confidence: 99%
See 2 more Smart Citations